The brass dolphin - Harvey, Caroline; Copyright Paperback Collection (Library of Congress) (New York : Berkley Books, 1997)
On the island of Malta during World War II, British nurse Lila Cunningham awaits the return of her love, a British soldier of noble birth. But will he marry a woman below his rank? Meanwhile, a native Maltese teacher pines for her.
Keywords: World War, 1939-1945 -- Malta -- Fiction; Historical fiction